Edukasi tentang Stunting pada Ibu Hamil dan Pasangan Produktif dibawah 35 Tahun - Adi Nurapandi; Yuyun Rahayu; Ima Sukmawati; Nabil Ridla Firdaus (Yayasan Inspirasi El Burhani, 2022)
Introduction: Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time. The survey proves that in 2019, 30 percent of Indonesian children under five were stunted. This condition can be caused by many aspects, from education to economic aspects. Stunting is very important to prevent because it will have an impact on the future of the child and is difficult to fix. One of the actions that can be taken is increasing knowledge about stunting to the community to reduce the incidence of stunting in the community. Objective: to provide education about stunting to pregnant women and productive couples under the age of 35 years in Cisaga District, Ciamis Regency. Method: The method in this activity is counseling, delivery using audio-visual and multimedia effects so that the material can be easily understood by educational participants. Result: The success of this service can be seen from the enthusiasm and enthusiasm of pregnant women and productive couples who play an active role in participating in activities and can answer evaluations of the material that has been delivered. Conclussion: The implementation of this service activity has been carried out smoothly, all participants can understand and are committed to implementing all the recommendations to prevent stunting.